Emancipation and creativity atlas - Pinto, António Gorgel (My University, 2021)
Participatory art and design is an eclectic domain and an increasingly relevant trend. We have been witnessing the profusion of projects of an activist nature, simultaneously informed by ethics, aesthetics and politics, which aim to benefit society. Encouraging the social and cultural sustainability of citizens living in disenfranchised residential areas by developing their creativity in a systematised way is the scope of the present research. Through an experimental methodology focused on project development, three case studies are presented—Netskola, Kowork and More South—all of which took place in socially and culturally disenfranchised neighbourhoods of the wider Lisbon area, specifically in the cities of Amadora and Oeiras. Then follows a case study evaluation conducted using the Delphi method. The research concluded that participatory art and design is a holistic territory that can be understood as interdisciplinary or transdisciplinary and that this understanding can foster the development of alternative and innovative solutions that contribute to the sociocultural sustainability of vulnerable urban areas. Recognising the advantage of this expanded field and enhancing the socially engaged art domains is not only important for these areas of knowledge, which can thus develop further, but also for the many situations in society that can benefit from systematic creativity.
Keywords: Innovation; Transmedia practice; Co-design; Activism; Societal image